POHON AREN SEBAGAI TANAMAN FUNGSI KONSERVASI - Erni Mulyanie; Andhy Romdani (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2017)
Cimanggu is the largest villages in Kecamatan Langkaplancar and still has many palm trees. These potentials need to be conserved to ensure environmental sustainability and the welfare of surrounding communities. Efforts to maintain its sustainability is to sharing knowledge and understanding of the importance of palm trees existence as a erosion or landslide conservation plant to be developed or cultivated in earnest by various parties. The purpose of this research is to know the benefits factors of sugar palm tree (Arenga Pinnata) as a conservation plant function in the Cimanggu Village Langkaplancar Pangandaran District. The research method is quantitative descriptive research. In addition, the authors also use the data survey because to generate quantitative data, also illustrates the sample studied. The results showed that the palm trees (arenga pinnata) have benefits as a plant conservation in the Cimanggu Village Langkaplancar Pangandaran District. Cimanggu village is eligible to grow palm trees that able to prevent floods and landslides. Besides, palm trees that can grow well on the cliffs will be very good as erosion prevention or landslides.